Kepastian Hukum Bagi Investor Asing di Indonesia: Analisa Hukum Berdasarkan Undang-Undang Nomor 25 Tahun 2007 Tentang Penanaman Modal - Prayudha, Eko Irianto (LPPM Institut Pendidikan Nusantara Global, 2025)
In domestic economic development, the Government of Indonesia opens opportunities for investors, both domestic and foreign, to participate in strategic projects, through investment. Regarding Investment from Foreign Investors, Indonesia acts as a Host State or Capital Recipient State to regulate the